Economic Analysis of Red Tilapia (Oreochromis sp.) Production Under Different Solar Energy Alternatives in a Commercial Biofloc System in Colombia † - Cala-Delgado, Daniel Leonardo [UNESP]; Ismael da Costa, Jesaías; Garcia, Fabiana [UNESP] (MDPI, 2024)
The study investigates the economic aspects of red tilapia (Oreochromis sp.) production using biofloc technology under different electrical energy sources. Conducted at the El Vergel Fish Farming Association in Arauca, Colombia, the study examines four energy treatments: conventional energy (CE), combined conventional and photovoltaic energy (CPVE), full photovoltaic energy (PVE), and simulation of photovoltaic energy generating surplus for nighttime use (PVES). The water quality and zootechnical performance met the species requirements, with dissolved oxygen decreasing as fish size increased. The PVE treatment had the highest initial investment due to solar panels and battery costs, but it also had the lowest operating energy costs. However, the overall costs of the PVE treatment increased due to depreciation and maintenance. Feed was the largest production cost, followed by labor in most treatments, while depreciation was a major cost for the PVE treatment. The total operating cost (TOC) of the photovoltaic energy systems (PVE and PVES) was lower compared to that of conventional energy (CE), with PVES showing the highest cost savings. The reduction in energy costs highlights the potential for solar energy systems to enhance the economic viability of aquaculture production, making these systems a favorable option for sustainable production in the long term.
Keywords: aquaculture; BFT; photovoltaic energy; selling price; solar panels